2008
DOI: 10.1016/j.eurpsy.2008.01.464
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy reduces depression symptoms in people with a traumatic brain injury: Results from a pilot study

Abstract: Background and Aims:Major depression is a significant problem for people with a traumatic brain injury (TBI) and its treatment remains difficult. A promising approach to treat depression is Mindfulness-based cognitive therapy (MBCT), a relatively new therapeutic approach rooted in mindfulness based stress-reduction (MBSR) and cognitive behavioral therapy (CBT). We conducted this study to examine the effectiveness of MBCT in reducing depression symptoms among people who have a TBI.Methods:Twenty individuals dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The approach has been consistently effective in preventing relapse in individuals with recurrent depression 16,[18][19][20] and is a recommended therapy for relapse prevention in the United Kingdom. In both studies, we found improvements in health status and depression symptoms, 22,23 which were maintained at 1-year follow-up. 22,23 In the first study, we used a 12-week intervention primarily focused on mindfulnessbased stress reduction.…”
Section: E14mentioning
confidence: 60%
See 1 more Smart Citation
“…The approach has been consistently effective in preventing relapse in individuals with recurrent depression 16,[18][19][20] and is a recommended therapy for relapse prevention in the United Kingdom. In both studies, we found improvements in health status and depression symptoms, 22,23 which were maintained at 1-year follow-up. 22,23 In the first study, we used a 12-week intervention primarily focused on mindfulnessbased stress reduction.…”
Section: E14mentioning
confidence: 60%
“…17 Individuals are taught, by developing a greater awareness of thoughts and feelings, to decenter from problematic thoughts by viewing them as mental events rather than as accurate reflections of reality. 22,23 In the first study, we used a 12-week intervention primarily focused on mindfulnessbased stress reduction. 21 The potential of mindfulness-based interventions in reducing symptoms of depression, preventing relapse, and the relative cost advantage provided by the group format led us to examine the feasibility and potential effect of a modified MBCT program for individuals with a TBI in 2 pilot studies.…”
Section: E14mentioning
confidence: 99%
“…In addition, preliminary data support the effectiveness of treatments that involve a combination of biofeedback and virtual reality (Grade of recommendation: GPP) (Shiri et al, 2013 ). Research to support the effect mindfulness-based interventions on post-traumatic headache is still ongoing (Grade of recommendation: GPP) (Bédard et al, 2012 ). Finally, one study supports the use of hypnosis for the treatment of pain in post—concussion syndrome (GPP) (Dilks and Bourassa, 2012 ).…”
Section: Evidences and Discussionmentioning
confidence: 99%
“…MM has also been successfully applied to clinical populations dealing with similar symptoms. An RCT demonstrated positive benefits of meditation in persons with multiple sclerosis (Grossman, et al, 2010), and studies with less rigorous methodologies have shown benefits of meditation in traumatic brain injury (Bedard et al, 2012; Johansson, Bjuhr, & Ronnback, 2012) and stroke (Johansson, et al, 2012; Lawrence, Booth, Mercer, & Crawford, 2013). MM training has also been explored in people with aphasia resulting in improved reaction times in a cognitive task (Orenstein, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%